Do Auctioneers Pick Optimal Reserve Prices? - Davis, Andrew M.; Katok, Elena; Kwasnica, Anthony M. (Management Science, 2011)
We investigate how auctioneers set reserve prices in auctions. A well-established theoretical result, assuming risk neutrality of the seller, is that the optimal reserve price should not depend on the number of participating bidders. In a set of controlled laboratory experiments, we find that seller behavior often deviates from the theoretical benchmarks. We extend the existing theory to explore three alternative explanations for our results: risk aversion, anticipated regret, and probability weighting. After fitting our data to each of these models through parameter estimation techniques on both an aggregate and individual level, we find that all three models are consistent with some of the characteristics of our data, but that the regret model provides a slightly more favorable fit overall. This paper was accepted by Teck-Hua Ho, decision analysis.